2015
DOI: 10.15406/jpcpy.2015.03.00149
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion, Vision and Touch in Movement Learning Neuroplasticity and the Mirror Neuron System

Abstract: The brains ability to restructure, linked with positive emotional states and techniques to enhance the activation of the mirror neuron system, allows for increased motor learning. This study examines the effects of enhancing goal-oriented movement and examines various techniques used to strengthen neural networks during such movement practices. Goal oriented movement practices are commonly used when engaging in Pilates. Participants will be divided between three groups to help identify potential differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Dalam studi sebelumnya didapatkan bahwa dalam pembelajaran sistem sensorik, emosi yang terkait dengan masukan sensorik seperti penglihatan (visual) dapat lebih meningkatkan penerimaan ke daerah motorik (Masterson, 2015). Mekanisme cermin juga ada di insula dan rostral cingulate, yaitu mengubah situasi emosional yang diamati menjadi respons motorik viskositas yang serupa dengan yang ada ketika seseorang benarbenar mengalami emosi tersebut (Chen et al, 2017).…”
Section: Pembahasanunclassified
“…Dalam studi sebelumnya didapatkan bahwa dalam pembelajaran sistem sensorik, emosi yang terkait dengan masukan sensorik seperti penglihatan (visual) dapat lebih meningkatkan penerimaan ke daerah motorik (Masterson, 2015). Mekanisme cermin juga ada di insula dan rostral cingulate, yaitu mengubah situasi emosional yang diamati menjadi respons motorik viskositas yang serupa dengan yang ada ketika seseorang benarbenar mengalami emosi tersebut (Chen et al, 2017).…”
Section: Pembahasanunclassified
“…Improved muscle strength and endurance can enhance functional mobility and make daily activities easier to perform [8]. Also, may promote neuroplasticity, by engaging in repetitive and task-speci c movements, individuals with PD may facilitate neural adaptation and improve motor function over time [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above, we also found that, for the EG alone, a change in EI (emotion perception accuracy) was predictive of ML at post-test There have been myriad of studies linking emotion and emotion regulation to enhanced motor learning, control, performance (Beatty et. al., 2014;Masterson, 2015;Coombes et. al., 2005) and even muscle afferent firing (Ackerly et.al., 2017).…”
Section: Ei Measuresmentioning
confidence: 99%
“…Examples of where this might come into play in our task, could be the point where the participant starts reaching towards the target as soon as it appears, or when they overcome the rotation to move towards the target. There appear to be common brain regions (like the dorsomedial prefrontal cortex and left ventral premotor cortex) and neurological mechanisms underlying both emotional processes, movement planning and execution of action (Masterson, 2015;Beatty et. al., 2013;Mogenson et al, 1980;Coombes et al, 2012).…”
Section: Ei Measuresmentioning
confidence: 99%